(untitled) (Pakistan Journal of Science, 2022)
The present study was designed to evaluate the quality of traditional and commercial yoghurt brands and to acknowledge their health benefits for human consumption in district Rawalpindi. Nine types of samples collected from different resources were divided into three categories. A, B and C were from cow, buffalo, and mixed (cow and buffalo) samples respectively. D, E, and F were from local vendors while G, H, and I were from different commercial yogurt brands. These samples were evaluated thrice on weekly basis using standard protocols for sensory, physicochemical, and microbiological attributes. It was concluded from the current study that the overall acceptability of commercial brand yoghurt was higher as compared to traditional ones. Physiochemical analysis of commercial yoghurt samples was consistent and showed a slight variation as compare to traditional yoghurt. Microbiological analysis revealed that total bacterial count of commercial yoghurt was lower as compared to traditional ones.